Girls who code : learn to code and change the world - Saujani, Reshma (Puffin Books, 2018)
Introduces computer coding to young girls, offering insights and anecdotes from notable female coders working at places such as Pixar and NASA. Offers activities and illustrations to showcase techniques, languages, and technology in coding.